2021
DOI: 10.1177/20503121211029179
|View full text |Cite
|
Sign up to set email alerts
|

Barriers toward the practice of healthy behaviors among patients with non-communicable diseases in Gaza Strip, Palestine

Abstract: Objectives: Non-communicable diseases are non-infectious health conditions caused by genetic, physiological, environmental, and behavioral factors. Currently, non-communicable diseases account for almost two-thirds of deaths globally. This study aimed to explore the patients’ adherence level to the key recommendations, and the main barriers toward the practice of healthy behaviors among non-communicable diseases patients. Method: This cross-sectional study was conducted among a representative sample of non-com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Many studies were conducted by researchers worldwide and focus on healthcare professionals' adherence to counseling on healthy behaviors for NCDs patients from healthcare professionals' perspectives, as well as, from the patients' perspectives ( 14 , 19 , 20 ). In the Palestinian context, there are many studies conducted to investigate the healthcare professionals' adherence to educate healthy behaviors to patients with NCDs from healthcare professionals' perspective, but little is known whether patients with non-communicable diseases receive advice on health behaviors from healthcare professionals ( 10 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies were conducted by researchers worldwide and focus on healthcare professionals' adherence to counseling on healthy behaviors for NCDs patients from healthcare professionals' perspectives, as well as, from the patients' perspectives ( 14 , 19 , 20 ). In the Palestinian context, there are many studies conducted to investigate the healthcare professionals' adherence to educate healthy behaviors to patients with NCDs from healthcare professionals' perspective, but little is known whether patients with non-communicable diseases receive advice on health behaviors from healthcare professionals ( 10 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted showed that 87.5% of health care professionals claimed that they are sometimes or always adherence to counseling on healthy behaviors in terms of physical activity, 80.5% in terms of a healthy diet, 54.8% % in terms of stop tobacco, and 82.7% in terms of attending medical follow-up based on WHO-PEN protocol 2 ( 13 ). Besides, another study conducted among patients with NCDs in Gaza Strip showed that 50.1% claimed that they are committed to healthy behaviors in terms of physical activity and 44.04% in terms of o a healthy diet ( 14 ). There are a lot of studies concerned with professionals' adherence to advice on healthy behaviors from the health professionals' perspective, but little is known whether patients with non-communicable diseases receive advice on health behaviors from healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the evidence of the benefits of PA in growth and development, can make individuals better physically and mentally, and reduce the risk of many non-communicable diseases, the literature assumed that regular PA is important for resilience against COVID-19, and it has a therapeutic effect on the immune system. [46][47][48]…”
Section: Impact Of the Covid-19 Pandemic On The Prevalence Of Pamentioning
confidence: 99%
“…The five PHCs were selected purposively from the Gaza Strip. One center in each governorate according to inclusion criteria: (1) had all the health education about the healthy behaviors suggested by the WHO-PEN 2 protocol, and (2) were classified as having low adherence to healthy behaviors according to the quantitative part of the study [13,14].…”
Section: Sampling and Participantsmentioning
confidence: 99%
“…Based on HBM and TPB, there were seven main determinants of human behaviors include perceived self-efficacy, perceived social acceptability, perceived action efficacy, cues for action, accessibility of materials, perceived susceptibility, and perceived severity [15,17]. Certain questions related to some main significant and insignificant previous quantitative results were involved [14]. The interview guides were developed and used to confirm that data on the identical overall areas were gathered from each participant, whereas permitting a degree of freedom and adaptability in getting the material from the participants [18].…”
Section: Interview Guide and Data Collectionmentioning
confidence: 99%